Thermal comfort analysis of office spaces at Gombak library, International Islamic University Malaysia, - Musbawu, Ganiyu Amao (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
The thermal comfort of a person is the condition of mind that expresses satisfaction with the thermal environment that plays a significant role in determining building occupant performance, productivity and energy efficiency. The ASHRAE Standard 55-2013 has opined that the maintenance of an indoor environment that is thermally acceptable by over 80% of the occupants will result in optimizing indoor space with the overall benefit to occupants' well-being, productivity and economic benefits. Therefore, the International Islamic University, Malaysia (IIUM) will be aligned on the path of achieving the requirements of Malaysia's green building index (GBI) when the library office space meets the conditions of thermal comfort. The study aims to investigate the effect of indoor environmental conditions on the thermal comfort of the staff of the IIUM library. The methodology adopted for the survey involves the concurrent measurement of environmental and personal variables through observations and user questionnaire survey respectively. The environmental variables include air temperature (oC), relative humidity (%), air velocity (m/s) and radiant temperature (oC) while the personal variables are metabolic rate (met) and clothing (clo). The data were collected from 29th to 31st of July 2015 (3 days) to coincide with the driest month of the monsoon season in Malaysia. Forty-four staff of the IIUM library involved in the survey completed a total of 528 responses across nine air-conditioned office space with four responses from each respondent per day, a concurrent measurement of the environmental variables were carried out for the duration of the survey. In line with best practice, the ASHRAE thermal comfort tool and descriptive statistics were used for the analysis of results. The thermal comfort tool allows for the determination of the synergetic impact of the environmental variables and personal variables on thermal conditions. In general, the findings show that the subjective response using the thermal sensation and thermal comfort scale fails to meet the minimum vote of 80% satisfaction, this finding was in tandem with the office space observed microclimate failure to satisfy standards requirement. Similarly, the PMV and PPD of -0.54 and 11% respectively are determined with the ASHRAE thermal comfort tool which failed to meet the minimum requirement for satisfaction. Finally, the study shows that the thermal comfort zone temperature was identified to be within the range of 22.9oC to 26.4°C and relative humidity of 69% to 73.5% while the average clothing value was 0.61 clo. Conclusively, the comparison of the thermal conditions (user's questionnaire survey and objective measurement) observed between the different office space and across the four floors show that the building's indoor thermal conditions was uncomfortable by failing to meet the requirements of both MS-2014 and ASHRAE Standard 55-2013. Keywords: Thermal comfort, Thermal sensation, Comfort zone, Library, offices, Staff.